2022
DOI: 10.1017/hpl.2022.31
|View full text |Cite
|
Sign up to set email alerts
|

Transverse mode instability mitigation in a high-power confined-doped fiber amplifier with good beam quality through seed laser control

Abstract: In this work, the confined-doped fiber with the core/inner-cladding diameter of 40/250 µm and a relative doping ratio of 0.75 is fabricated through the modified chemical vapor deposition method combined with the chelate gas deposition technique, and subsequently applied in a tandem-pumped fiber amplifier for high power operation and transverse mode instability (TMI) mitigation. Notably, the impact of the seed laser's power

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…At the same pump wavelength, although the beam quality of the output laser may be slightly degraded (affected by fiber fusion), the improvement of the maximum output power also brings the improvement of the brightness of the laser. In fact, similar abnormal TMI phenomena were reported as early as 2019, and in recent years, there have been reports of increasing the TMI threshold by introducing higher order modes [89][90][91]. In [90], they believe that introducing higher-order modes The results are shown in Table 5.…”
Section: Abnormal Tmi Suppression Methods Based On Fiber Coilingsupporting
confidence: 59%
See 2 more Smart Citations
“…At the same pump wavelength, although the beam quality of the output laser may be slightly degraded (affected by fiber fusion), the improvement of the maximum output power also brings the improvement of the brightness of the laser. In fact, similar abnormal TMI phenomena were reported as early as 2019, and in recent years, there have been reports of increasing the TMI threshold by introducing higher order modes [89][90][91]. In [90], they believe that introducing higher-order modes The results are shown in Table 5.…”
Section: Abnormal Tmi Suppression Methods Based On Fiber Coilingsupporting
confidence: 59%
“…In fact, similar abnormal TMI phenomena were reported as early as 2019, and in recent years, there have been reports of increasing the TMI threshold by introducing higher order modes [89][90][91]. In [90], they believe that introducing higher-order modes The results are shown in Table 5. With the increase of fiber coiling diameter, the TMI threshold of the laser increases gradually.…”
Section: Abnormal Tmi Suppression Methods Based On Fiber Coilingsupporting
confidence: 59%
See 1 more Smart Citation
“…In our recent study [45], the TMI threshold is experimentally found to be closely related to the high-order mode (HOM) content of the seed laser. Further theoretical analysis indicated that by introducing incoherent HOM content (with the same frequency as the fundamental mode) into the fiber amplifier, the gain of anti-Stokes HOM (coherent HOM) in the amplifier could be suppressed through transverse mode competition, which leads to a weaker interference between the FM and coherent HOM, thus facilitating a higher TMI threshold.…”
Section: Controlling the Seed Laser's Mode Puritymentioning
confidence: 97%
“…Fiber lasers have various applications owing to their high conversion efficiency, beam quality, compactness, and reliability 1 5 However, with an increase in the optical power, a series of unwanted nonlinear effects emerge. Specifically, stimulated Brillouin scattering (SBS) is the primary obstacle in scaling the power of narrow-linewidth lasers 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%